Implant placement in post-extraction sites : treatment options - Chen, Stephen T; Buser, Daniel (Quintessence Publishing, 2008)
Implant dentistry has become a standard option for the rehabilitation of fully and partially edentulous patients. With the ever-increasing number of dentists involved in implant dentistry, it is essential to ensure that their treatment methods follow the highest standard. The ITI Treatment Guide series, a compendium of evidence-based implant-therapy techniques in daily practice, is written by renowned clinicians and provides a comprehensive overview of various therapeutic options. Using an illustrated step-by-step approach, the ITI Treatment Guide shows practitioners how to manage different clinical situations, with the emphasis on sound diagnostics, evidence-based treatment concepts, and predictable treatment outcomes. This third volume of the ITI Treatment Guide series provides clinicians with practical clinical information that will allow them to make evidence-based decisions regarding appropriate implant placement protocol in post-extraction sockets. The book features 15 case presentations illustrating the use of various clinical protocols as well as discussion of the factors influential to treatment outcome and potential complications.
ITI treatment guide ; Vol. 3
Keywords: Oral Surgical Procedures; Tooth Extraction; zubní implantáty jednotlivých zubů; Dental Implants; implantace zubů; Dental Implants, Single-Tooth; zubní lékařství; Dental Implantation; stomatochirurgické výkony; zubní implantáty; extrakce zubů